Social Representations of Domestic Animal Abuse and Neglect. General Aspects to Develop a Successful Awareness Campaign - Abifandi-Cedeño, Julia Dolores; Murillo Párraga, María Viviana; Espinosa Briones, David Orlando; Nagua-Jiménez, Luís Felipe (Journal of the University of Zulia, 2024)
The validity of social representations studies is largely the result of their ability to build epistemological bridges between the subjective dimension of knowledge in general and the objective realities of a given society. Under this premise, the objective of the research was to describe the social representations of mistreatment and abandonment of domestic animals, as a condition of possibility to structure a successful awareness campaign that, on the one hand, exposes the suffering of domestic animals before the problem of their abandonment by unscrupulous people and; on the other hand, serves to identify the social affectations that have the mistreatment and abandonment of animals. Methodologically, the research used documentary research techniques and a post-anthropocentric philosophical view. In conclusion, social awareness campaigns play an important role in the prevention of animal abuse and neglect. To be successful, these initiatives must adopt a multidisciplinary approach that combines communication, education, and community participation strategies.